Loka paramparā te kabīlā sabhiācāra - Kazāka, Kirapāla (Nawīṃ Dillī : Sapata-Sindhū Pabalīkeshanaza, 1994)
Articles on the social life and customs of various tribes of India.
In Panjabi.
Mode of access: Internet.
Keywords: India -- Social life and customs; India -- Scheduled tribes